2000
DOI: 10.1515/bc.2000.037
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence between a 55 kDa Protein (p55) and a 12 kDa Protein (p12) in Facilitating the Nuclear Entry of Goat Uterine Estrogen Receptor under Cell-Free Conditions

Abstract: A 55 kDa nuclear localization signal binding protein (p55) is involved in the transport of the goat uterine estrogen receptor from the cytoplasm to the nuclear pore complex (NPC). p55 forms a complex with a 12 kDa protein (p12) which in turn becomes 'docked' at the NPC. The present study reports on the purification and functional characterization of p12. Both p55 and p12 are Mg2+-dependent ATPases. The protein-protein interactions that take place between these two molecules at the NPC cause an enhancement in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The progesterone receptors apparently have the capacity to efflux from the nucleus under some conditions of ATP depletion while glucocorticoid receptors that are imported to the nuclei appear to remain within that compartment upon ATP depletion [Guiochon‐Mantel et al, 1991; Hu et al, 1994]. The role of ATP in estrogen receptor nuclear import pathway has been studied earlier [Sai Padma and Thampan, 2000]. The involvement of ATP hydrolysis for nuclear export was addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The progesterone receptors apparently have the capacity to efflux from the nucleus under some conditions of ATP depletion while glucocorticoid receptors that are imported to the nuclei appear to remain within that compartment upon ATP depletion [Guiochon‐Mantel et al, 1991; Hu et al, 1994]. The role of ATP in estrogen receptor nuclear import pathway has been studied earlier [Sai Padma and Thampan, 2000]. The involvement of ATP hydrolysis for nuclear export was addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicated that p66 was in a position to interact with both ap55 and E‐RAF. Previous reports published from this laboratory demonstrated the existence of a 55 kDa protein that transports the regular estrogen receptor to the goat uterine nucleus [Nirmala and Thampan, 1995; Sai padma and Thampan, 2000] and a 62 kDa protein that transports the naER to the nucleus [Sreeja and Thampan, manuscript communicated]. It was decided to check the possibility whether the 66 kDa protein identified in the present study is the much sought after transport protein that transports E‐RAF to the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Purification of p12 was achieved following the method described by Sai Padma and Thampan [2000]. p12 is the nuclear pore complex-associated protein that binds p55.…”
Section: Preparation Of Affinity Matricesmentioning
confidence: 99%